Socio-Political Risk Management Assessing and Managing Global Insecurity - Engemann, Kurt J.; Lavery, Cathryn F.; Sheehan, Jeanne M. (Developments in Managing and Exploiting Risk, 2023)
This volume explores the understanding, analysis and applications of mitigating social and political risks and the devastating consequences of mishandling of incidences. Contributors use evidence based practices, theories and real-life scenarios to explore how social and political risk mitigation is essential for the survival of an organization and how positive restructuring can take place after negative consequences occur.